Study of Noun Phrase in Urdu - Aasim Ali; Mohammad Kamran; Shahid Siddiq; Sarmad Hussain (Linguistics and Literature Review, 2016)
This paper presents discussion of internal structure of Noun Phrase (NP) in Urdu. It also proposes a computational grammar using LFG (Lexical Functional Grammar) formalism.